How far are the transition countries from the economic standards of the European Union?: Measuring efficiency and growth in agriculture - Lissitsa A. (2014)
Economic reforms in the Central and East European countries in the 1980s helped to transform the structure and volume of agricultural production, consumption, and trade, resulting in significant improvements in agricultural productivity. However, the transition countries differ greatly in the magnitude and direction of these changes. This study measures and compares the levels and trends in agricultural productivity in transition countries with those of EU countries, making use of the most recent data available from the Food and Agriculture Organization (FAO). This study employs a nonparametric distance-function approach to measure a Malmquist productivity index as well as the magnitude and direction of technological change. The Malmquist productivity index is decomposed into changes in technology and technical efficiency. The measures provide insightful information for researchers in designing policies to achieve a high growth rate in transition countries. ? 2007 M.E. Sharpe, Inc. All rights reserved.